The role of vitamin D in multiple sclerosis and its mechanisms of action - Kowalczyk, Agata; Kiełbasa , Justyna; Przestrzelska, Magda; Rykucka, Aleksandra; Wąs, Marcin; Zozula, Natalia; Tomczewska, Zuzanna; Bil, Katarzyna; Ślesicka, Iga; Latała, Aleksandra (Quality in Sport, 2024)
Introduction and Purpose: Multiple sclerosis (MS) is a prevalent autoimmune disease affecting the central nervous system, particularly in young people. Characterized by neurodegenerative and demyelinating processes, MS is influenced by genetic and environmental factors. Research indicates that sufficient levels of vitamin D can reduce the risk of developing MS. Studies show that higher sun exposure and dietary vitamin D intake are associated with a lower incidence of MS. Moreover, vitamin D supplementation may benefit those already diagnosed by alleviating symptoms and improving their quality of life. This review explores the potential benefits of vitamin D and its neuroprotective mechanisms in MS. State of Knowledge: MS research and treatments have focused on immunomodulation, with less emphasis on neuroprotection, including the role of vitamin D. It is well-established that vitamin D has anti-inflammatory effects on the immune system in MS. It influences the proliferation and differentiation of neural stem cells and oligodendrocytes, enhances neurotrophin expression, reduces reactive astrogliosis, decreases oxidative stress, and stabilizes the blood-brain barrier. Research suggests that adequate vitamin D levels and supplementation might improve MS outcomes. Conclusion: New diagnostic tools and therapeutic strategies are urgently needed to address the complex nature of MS, which includes inflammation, neuronal death, demyelination, and oxidative stress. Promoting vitamin D sufficiency and supplementation, alongside developing new neuroprotective agents, remains a valuable approach in combating MS. Understanding the mechanisms of MS and the effects of vitamin D could lead to better management strategies and enhanced quality of life for patients.